Measuring Covid 19 Vaccine Intentions: Extending the Theory of Planned Behavior - Julina, Julina; Pratiningsih, Vony (ADPEBI, 2022)
This study attempts to extend the Theory of Planned Behavior (TPB) by adding a company reputation variable. Data was collected using a questionnaire distributed online. The questionnaire consists of several sections where the first section discusses demographics and the next section discusses the variables studied, namely attitudes, subjective norms, perceived behavioral control (PBC), corporate reputation, and intention to participate in vaccines. The data were tested for validity and reliability before being tested for multiple linear regression. The results found that attitudes and PBC had a positive and significant effect, while subjective norms and corporate reputation had a positive but not significant effect. This shows that the respondents in this study intend not because of the influence of the people around them and also the company's reputation. Even though vaccine providers consist of several companies and cause many differences in perceived quality, this does not significantly affect respondents' intentions.